Different Academic Coping Strategies Facing Online Learning During Covid-19 Pandemic Among the Students In Counselling Department - Umar, Nur Fadhilah; Sinring, Abdullah; Aryani, Farida; Latif, Suciani; Harum, Akhmad (Indonesian Journal of Educational Studies, 2021)
The challenge for academic success in higher education is getting tougher with the implementation of study from home (SFH) in the covid-19 pandemic. One aspect that supports the success of online learning is the ability of students to survive in difficult conditions or referred to as coping skills. Coping skills consist of several strategies, divided into positive and negative coping strategies. The objectives of this study: 1) are there any differences in student coping strategies in dealing with online learning during the covid-19 pandemic; 2) are there differences in student approach strategies in dealing with online learning during the covid-19 pandemic; 3) Are there differences in student avoidance strategies in dealing with online learning during the covid-19 pandemic; and 4) Are there differences in student social support strategies in dealing with online learning during the covid-19 pandemic. This type of research is a type of descriptive research. The sample in this study were students of the guidance and counseling study program enrolled in the 2020/2021 academic year. The research sample is 210 consisting of 100 male students and 110 female students who were selected randomly. The instrument of this study used an Academic coping strategies questionnaire from Sullivan (Sullivan, 2010) adapted. The results of the adaptation of the ACSC questionnaire through the CFA (Confirmatory Factor Analysis) test showed the Cronbach alpha value = 0.081; RMSEA = 0.072; CFI= 0.98; GFI= 0.882; CMIN/DF = 2548.63/1540; and TLI = 0.891. The results of data analysis using the ANOVA test shows the approach factor is the type of coping strategy that is most widely used by students during online learning. The coping approach strategy is most often used by students in the category of academic achievement of the five best in class.